Task scheduling mechanisms in fog computing: review, trends, and perspectives - Yang, Xin; Rahmani, Nazanin (Kybernetes, 2021)
Purpose In the past, with the development of the internet of things (IoT), this paper aims to consider fog computing (FC) as an efficient accompaniment to the cloud to control the IoT’s information and relation requirements. Wholly, FC is placed carefully around the IoT systems/sensors and develops cloud-based computing, memory and networking devices. Fog shares many similarities with the cloud, but the only difference between them is its location, in which fog devices are very close to end-users to process and respond to the client in less time. On the other hand, this system is useful for real-time flowing programs, sensor systems, and IoT that need high speed and reliable internet connectivity. However, there are many applications such as remote healthcare and medical cyber-physical systems, where low latency is needed. To reduce the latency of FC, the task scheduler plays a vital role. The task scheduling means to devote the task to fog resources in an efficient way. Yet, according to the findings, in spite of the preference of task scheduling techniques in the FC, there is not any review and research in this case. So, this paper offers systematic literature research about the available task scheduling techniques. In addition, the advantages and disadvantages associated with different task scheduling processes are considered, and the main challenges of them are addressed to design a more efficient task scheduler in the future. Additionally, according to the seen facts, future instructions are provided for these studies. Design/methodology/approach The paper complies with the methodological requirements of systematic literature reviews (SLR). The present paper investigates the newest systems and studies their practical techniques in detail. The applications of task scheduling mechanisms in FC have been categorized into two major groups, including heuristic and meta-heuristic. Findings Particularly, the replies to the project problem analyzed task scheduling are principal aim, present problems, project terminologies, methods and approaches in the fog settings. The authors tried to design his systematic discussion as precisely as possible. However, it might have still endured various confidence risks. Research limitations/implications This study aimed to be comprehensive but there were some limitations. First, the usage of affair scheduling in fog settings are contained in many places such as editorial notes, academic publications, technical writings, Web pages and so on. The published papers in national magazines were omitted. Also, the papers with the purpose of a special task scheduling issue, which probably consider other subjects rather than affair planning issue are omitted. So, in the competence of this study, this systematic analysis must be considered as the studies published in the central international FC journals. Second, the given issues might not have considered the general task scheduling area, which points to the possibility of describing more related questions that could be described. Third, research and publication bias: five confident electronic databases were chosen based on past study experiments. Finally, the numbers show that these five electronic databases must suggest the most related and reliable projects. Yet, selecting all main performing projects has not been confirmed. Probably some effective projects were omitted throughout the processes in Section 3. Different from the conclusion, changing from the search string to the information extraction exists, and the authors tried to exclude this by satisfying the source in central projects. Practical implications The results of this survey will be valuable for academicians, and it can provide visions into future research areas in this domain. Moreover, the disadvantages and advantages of the above systems have been studied, and their key issues have been emphasized to develop a more effective task scheduling mechanisms in the FC mechanisms. Originality/value It is useful to show the authors the state-of-the-art in the fog task scheduling area. The consequences of this project make researchers provide a more effective task planning approach in fog settings.